NAVIGATING THE BLUE PARADOX: POLICY, POWER, AND PARTICIPATION IN PAKISTAN’S MARITIME TOURISM (Contemporary Journal of Social Science Review, 2025)
Maritime (blue) tourism is now considered one of the fastest-growing sectors of the world tourism economy. It significantly contributes to the livelihoods of the coastal population, promotes economic diversification, and supports sustainable development. However, its potential as a key driver of socio-economic and environmental sustainability is often overlooked in the policy frameworks across many coastal nations in the Global South, including Pakistan. This qualitative study examines the governance, institutional, and community dimensions that can shape the sustainable development of blue tourism in Pakistan’s coastal regions. The primary data was collected through semi-structured interviews with key stakeholders, including industry experts, policymakers, and civic stakeholders (N=10). Thematic analysis of the interview data was performed to explore barriers and enablers of sustainable blue tourism. The study findings reveal that the policy effectiveness was undermined due to symbolic stakeholder engagement and elite-driven policy planning. The study highlights some community-led initiatives (although very small) that show the potential of participatory models to turn around conservation and livelihood diversification efforts. Utilizing Collaborative Governance and Stakeholder Theory as its theoretical foundation, the study finds that fragile collaborative mechanisms and misaligned power relations can influence sustainable tourism outcomes. The study recommends that a shift from centralized development agendas to grassroots-level models can provide the framework for socio-cultural and sustainable development in coastal regions. The paper contributes to the literature by integrating actor-level and governance-level perspectives on blue tourism in the context of the Global South and offers policy-relevant insights for strengthening institutional coordination, promoting inclusive governance, and advancing sustainable blue tourism development.